SCREENING OF INDONESIAN SINENSIS TEA CLONES (Camellia sinensis var. sinensis) FOR HIGH-QUALITY GREEN TEA: EMPHASIS ON INDONESIAN NATIONAL STANDARDS COMPLIANCE, HIGH PROTEIN, AND LOW CAFFEINE - M. Khais Prayoga; Koko Dwi Sutanto; Heri Syahrian; Vitria P. Rahadi; Bariza K. Humam; Dwinita W. Utami (Gunung Djati Conference Series, 2026)
Tea is one of the oldest beverages known to humanity, with green tea being among the most popular types due to its distinctive flavor and health benefits. The development of green tea is essential, both in terms of sensory quality and functional value. This study aimed to screen 35 Indonesian Sinensis tea clones to identify those with superior flavor, compliance with Indonesian National Standards (SNI), high protein content, and low caffeine levels. The research was conducted by processing fresh tea shoots into green tea, followed by quality evaluation based on SNI parameters, including moisture content, total ash content, crude fiber content, and polyphenol content, as well as analysis of protein and caffeine levels. The experiment employed a Randomized Complete Block Design (RCBD) with two replications and 35 clones as treatments. The results revealed significant variation in quality among the tested clones. Clone I.2.85 and II.2.108 was identified as the best-performing clone, meeting SNI quality standards (moisture content, total ash, crude fiber, and polyphenols), exhibiting high protein levels, low caffeine levels, and a premium flavor profile.